Potential drug interactions among people living with HIV on antiretroviral therapy in Belo Horizonte, Brazil - Alícia Moreira COSTA; Raissa Carolina CÂNDIDO; Letícia Penna BRAGA; Cássia Pinto MENDICINO; Cristiane Aparecida MENEZES-DE-PÁDUA (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To characterize the medication use profile and evaluate the factors associated with serious and contraindicated potential drug-drug interactions (DDIs) in pharmacotherapy of people living with HIV (PLHIV). Method: This is a cross-sectional study, comprising two moments in the trajectory of PLHIV treatment - baseline and reevaluation. Sociodemographic, clinical and therapeutic variables were obtained from medical records and interviews. The medications used were classified using the Anatomical Therapeutic Chemical (ATC) system and potential DDIs were identified and classified according to the severity and quality of documentation using Micromedex®. Descriptive analyses were carried out to characterize the selected variables and the logistic regression method was used for univariate and multivariate analyses. Results: At baseline (n=247), the mean age was 36.8 years, with 60.3% being male. Potential DDIs were observed in 84.2% of participants. Upon the reevaluation (n=100), the mean age was 53.0 years, with a male majority (54.0%). Potential DDIs were observed in 63.8% of participants. There was a reduction in the proportion of anti-infectives and an increase in cardiovascular medications, when comparing the baseline and reevaluation. The number of medications (> 3) and the antiretroviral regimen remained associated with the occurrence of potential serious and contraindicated DDIs. Conclusion: The profile of medications used reflected the pattern of the most prevalent diseases in the periods evaluated. There was a reduction in the mean number of medications used and, consequently, a reduction in the number of DDIs at both moments, including those of greater severity.